Evaluation of Antioxidative and Cytotoxic Activities of Streptomyces pluripotens MUSC 137 Isolated from Mangrove Soil in Malaysia - Ser, Hooi Leng; Ab Mutalib, Nurul Syakima; Yin, Wai Fong; Chan, Kok Gan; Goh, Bey Hing; Lee, Learn Han (Frontiers Media, 2015)
Streptomyces pluripotens MUSC 137 was isolated from mangrove soil obtained from Tanjung Lumpur, Pahang, Malaysia. We investigated the phylogenetic, genomic, biochemical, and phenotypic characteristics of this strain. Uniquely adapted microorganisms from mangrove habitats have previously yielded compounds of biopharmaceutical interest. In order to examine the bioactivities possessed by the strain, fermentation extract was prepared through solvent extraction method prior to bioactivities screenings. Antioxidant activity was examined via DPPH assay while the cytotoxic effect was assessed by means of examining the activity of the extract against selected human cancer cell lines, namely colon cancer cells (HCT-116, Caco-2, SW480, and HT-29), breast cancer cell (MCF-7), lung cancer cell (A549), prostate cancer cell (DU145), and cervical cancer cell (Ca Ski). The results revealed MUSC 137 possesses significant antioxidant activity and demonstrates cytotoxic effect against several cancer cell lines tested. The results indicated MCF-7 cells were most susceptible to the extract with the lowest IC50 (61.33 +/- 17.10 mu g/mL), followed by HOT-116 and A549. Additionally, selective index (SI) showed that MUSC 137 extract was less toxic against normal cell lines when compared to MCF-7 and HCT-116 cells. The extract was further subjected to chemical analysis using GC-MS and revealed the presence of deferoxamine and pyrrolizidines related compounds which may account for the antioxidant and cytotoxic properties observed.